Cirugía de la carótida extracraneana: Análisis de 100 casos consecutivos - Danza, Rómulo; Olivera, Daniel; Arias, José; Danza, Franco (Cirugía del Uruguay, 1977)
The authors analyze 100 cases of carotid surgery, operated between July 1967 and July 1976. CerebroVascular Insufficiency, with alteration of carotid caliber, was studied clinically and through arteriography, electroencefalogram and photoplethysmogram with compressions. Carotid atheromatosis ( 79 cases), stenosis of the lumen or ulcerated plates which act through the embolic mechanism, was treated by endarterectomy with longitudinal arteriotomy and, in the majority of cases, closure without patching. Transitory use of bypass was selective and solely in those cases in which monitoring indicated clamping ristk. inking of interna! carotid (19 cases) was treated by carotid shortening with termino terminal anastomosis. In carotid o bstructions in the low neck ( 2 cases) the procedure employed was extra-anatomic by-pass taking blood from another permeable artery at the low neck. Throughout the series there was only one case of operatory death ( a case of kinking); p·ost operatory R. DANZA Y COL. morbility was 5 % and was solved without problems with the exception of one case. Follow-up of patients for periods varying between 9 and 2 and a half years, showed 80 % satisfactory results, with disappearence or marked improvement of symptomatology and no new attacks.